2012
DOI: 10.1109/tbme.2011.2179299
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Ventilation $^3$He MRI for the Quantification of Disease in the Rat Lung

Abstract: Pulmonary diseases are known to be largely inhomogeneous. To evaluate such inhomogeneities, we are testing an image-based method to measure gas flow in the lung regionally. Dynamic, spin-density-weighted hyperpolarized (3)He MR images performed during slow inhalation of this gas were analyzed to quantify regional inflation rate. This parameter was measured in regions of interest (ROIs) that were defined by a rectangular grid that covered the entire rat lung and grew dynamically with it during its inflation. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…To achieve this, we utilized an animal model with a unilateral instillation of elastase, which results in tissue destruction and air trapping that physiologically imitates human emphysema (33). It is well known that heterogeneous emphysema results in inhomogeneous ventilation, as has been demonstrated with hyperpolarized 3 He MRI both in humans (34, 35) and unilaterally treated rats (36). It has also been shown that emphysema affects particle deposition patterns in small animal models (37, 38).…”
Section: Discussionmentioning
confidence: 86%
“…To achieve this, we utilized an animal model with a unilateral instillation of elastase, which results in tissue destruction and air trapping that physiologically imitates human emphysema (33). It is well known that heterogeneous emphysema results in inhomogeneous ventilation, as has been demonstrated with hyperpolarized 3 He MRI both in humans (34, 35) and unilaterally treated rats (36). It has also been shown that emphysema affects particle deposition patterns in small animal models (37, 38).…”
Section: Discussionmentioning
confidence: 86%
“…Hence, L m and D 2 have been traditionally adopted as a reference in previous studies on emphysema and COPD involving animal models. 15,24,27 However, a scale of severity had not been established for these metrics. This gap between airspace enlargement quantification and the degree of emphysema severity is overcome by the definition of the SI function, which provides a novel analytical expression for the interpretation of D 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the index D 2 , which takes into account the skewness of d, has shown to be more reliable than the others since it enables the identification of mild emphysema. 12 Indeed, D 2 has been used as the gold-standard metric for airspace enlargement quantification in the study of gas flow inside the lung tissue 15 or in the development of novel in vivo techniques of emphysema analysis based on microcomputed tomography (micro-CT). 2,19 It has been reported that larger values of D 2 are expected for areas of parenchymal tissue showing an increased enlargement of the airspaces as a consequence of emphysematous lesions.…”
Section: Introductionmentioning
confidence: 99%
“…However recently Kyriazis et al have noted that in a rat elastase model of emphysema ventilated by positive pressure and imaged using hp 3 He, inflation rates at the bases reduced more than at the apices compared to controls despite apparent diffusion coefficients (markers of emphysematous damage) indicating changes throughout the lung [68]. It is therefore possible that this was due to some inherent elastic property of the lung indicating underlying regional differences.…”
Section: Discussionmentioning
confidence: 99%